Effect of Nitrate on the Photochemical Production of Carbonyl Sulfide From Surface Seawater. Issue 13 (29th June 2022) - Li, Jian‐Long; Zhai, Xing; Du, Lin
Abstract: Carbonyl sulfide (COS) plays an important role in the sulfur cycle and climate change. Yet, much remains unknown about the photochemical mechanisms of COS in nutrient‐rich seawater. We measured the photochemical production rates of COS in the surface seawater of the Indian Ocean under sunlight irradiation. The photochemical production of COS was mainly initiated by ultraviolet (UV) radiation with UVA contributing approximately 68% to the total COS production. Using cysteine, a typical proxy of dissolved organic sulfur, the effect of enhanced nitrate concentration on COS formation was conducted in authentic seawater during simulated sunlight irradiation, indicating the enhancement of the COS formation with increasing nitrate concentrations. This result revealed that the generation of hydroxyl radical with nitrate photolysis plays a key role in the COS formation process. These findings improve our understanding of the marine COS photoproduction cycle and the impact of nitrate on the COS photochemical production in surface seawater. Plain Language Summary: Marine‐derived carbonyl sulfide (COS) contributes greatly to atmospheric sulfate formation, particularly in the stratosphere, and affects the climate. However, the effect of nitrate on the photochemical production of COS remains unknown. It is well‐known that nitrate is a major nutrient component and is ubiquitously distributed in seawater. The ultraviolet‐induced photolysis of nitrate to produce hydroxyl radical can substantially alter the oxidation balance of seawater and subsequently impact the marine environment. Our work reveals the pivotal role of hydroxyl radical in the COS formation process across surface seawater in the presence of enriched nitrate. Improvements to our understanding of the photochemical process of COS combined with enhanced water eutrophication are needed to better represent ocean sulfur cycling. Key Points: High production rates of carbonyl sulfide (COS) corresponded with high concentrations of chromophoric dissolved organic matter Ultraviolet radiation is the dominant driver of the photoproduction of COS in surface seawater Nitrate plays a critical role in promoting the photoproduction of COS in seawater